1990
DOI: 10.1021/bi00470a026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an anti-.alpha. monoclonal antibody on interaction of Escherichia coli RNA polymerase with lac promoters

Abstract: The anti-alpha monoclonal antibody, mAb 126C6, has been used to investigate the role of the alpha subunit in transcription initiation. mAb 126C6 strongly inhibits cAMP-CRP-dependent abortive initiation with lac P+, partially inhibits abortive initiation with the lac L8UV5 promoter, and is without effect on the d(A-T)n-directed synthesis of r(A-U)n. DNase I footprinting shows that the preformed mAb 126C6-RNA polymerase complex does not bind to cAMP-CRP-lac P+; RNA polymerase specific protection is largely lost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…For RNAPI and RNAPIII, it has been suggested that the role of one a subunit might be carried out by RPC40 whereas that of the other might be carried out by RPC19, which is also present in the polymerase complex at a stoichiometry of 1 (37). The finding that the two a subunits in E. coli RNAP are not functionally identical (140,141) supports the notion that RPC40 and RPC19, together, form the equivalent of the bacterial a dimer, even though they share only one of the four a-homology regions and that both proteins are structurally different outside of this region.…”
Section: Mutations In Subunits Of Eukaryotic Rnaps That Aresupporting
confidence: 57%
“…For RNAPI and RNAPIII, it has been suggested that the role of one a subunit might be carried out by RPC40 whereas that of the other might be carried out by RPC19, which is also present in the polymerase complex at a stoichiometry of 1 (37). The finding that the two a subunits in E. coli RNAP are not functionally identical (140,141) supports the notion that RPC40 and RPC19, together, form the equivalent of the bacterial a dimer, even though they share only one of the four a-homology regions and that both proteins are structurally different outside of this region.…”
Section: Mutations In Subunits Of Eukaryotic Rnaps That Aresupporting
confidence: 57%
“…region of the a subunit is available in the assembled RNA polymerase for interaction with other proteins. This same monoclonal antibody interferes with the interaction between the polymerase and the CRP-cAMP complex at the lac promoter, resulting in inhibition of transcription initiation (33). Although other interpretations have not been excluded, it is possible that binding of the antibody interferes with an interaction of the a subunit with CRP.…”
Section: Discussionmentioning
confidence: 99%
“…The OBS are of two motifs, F-boxes and C-boxes [14] and these boxes have different affinities for OmpR. Riftina et al [17] and Dalla Venezia and Krakow [18] were able to demonstrate inhibition of specific transcripts with monoclonal antibodies to alpha. The ompF promoter contains three contiguous F boxes and a C-box that is separate and downstream of the F-boxes.…”
Section: Introductionmentioning
confidence: 99%